PATH-32. BRAIN TUMOR CLASSIFICATION UPDATES FROM cIMPACT-NOW, THE CONSORTIUM TO INFORM MOLECULAR AND PRACTICAL APPROACHES TO CNS TUMOR CLASSIFICATION. (5th November 2018) - Louis, David; Brat, Daniel; Ellison, David
Abstract: cIMPACT-NOW (the Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy) was created to provide a forum to evaluate and recommend proposed changes to future CNS tumor classifications. While it is understood that the major impact on international brain tumor classification comes about through the WHO classification update process, it is anticipated that this additional process will see impact in selected tumor types and in time periods between the WHO classification updates. Over the past year, cIMPACT-NOW has convened three working committees (WC), each of which has focused on different classification issues. WC1 has debated the grading of diffuse gliomas relative to IDH status, and has formulated criteria for IDH-wildtype grade II and grade III diffuse astrocytic tumors that are likely to behave as glioblastomas, such as EGFR amplification and +7/-10 copy number changes. WC2 is developing a molecular classification of pediatric low-grade gliomas, focusing on the diffuse gliomas. WC3 has addressed miscellaneous issues, including clarifications of Not Otherwise Specific (NOS) and Not Elsewhere Classified (NEC) diagnoses and refined criteria for diffuse astrocytoma (e.g., the use of ATRX and p53 immunohistochemistry relative to 1p/19q testing) and diffuse midline glioma, H3 K27M-mutant. To date, two publications have resulted from WC3 and guidelines are expected soon from WC1 and WC2. The combined recommendations of the current cIMPACT-NOW WCs will be discussed in light of the WHO classification.